Effect of Metformin and Glimepiride on Glycated Haemoglobin and Lipid Profile Levels in Patients with Type 2 Diabetes Mellitus: Metformin and Glimepiride on Glycated Haemoglobin and Lipid Profile Levels in Patients with Type 2 DM (Journal of Bio-Science, 2026)
This study examined the effects of metformin and glimepiride on glycated hemoglobin (HbA1c) and lipid profiles in patients with type 2 diabetes mellitus (T2DM). The study was conducted over six months in an outpatient diabetes clinic. It includes adults aged 18-70 with HbA1c levels between 7% and 10%. Participants were treated with metformin (500-1000 mg) or glimepiride (1-4 mg), with dose adjustments based on glycemic control. HbA1c, fasting blood glucose, and lipid profiles were assessed at baseline and after six months. The results showed significant improvements in HbA1c, lipid profiles, mental health, and patient satisfaction. HbA1c levels decreased from 7.02% to 6.23% (p